Effect of paclobutrazol on root activity of mango (Malzgifera indica) - KOTUR, S C (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2004 at Bangalore on the effect of paclobutrazol applied@3.75 ga i/tree on the root activity distribution of] 9-year-old 'Alphonso' mango (Alangi/era indica L.) trees in the rooting volume of 240 cm radius from trunk and 50 cn depth using soil injection technique of 32p as the tracer. The intensity of root activity significantly declined to 575-9086 dpmg dry matter under paclobutrazoI application from 910-10739 under control during 15-60 days after application of the tracer. The active roots of mango trees were relatively uniformly distributed throughout the soil volulne under control compared to when paclobutrazol was applied. In the latter treatment, the active roots significantly bunched toward the trunk and close to soil surface leading to nearly one-half of the roots (44.56-58.02%) migrate to the zone of 80 cm distance and 25 cm depth. Consequently, farther distance and deeper rooting volume of the soil showed significantly sparser root activity. These results call for a more detailed investigation to evaluate the effect ofpaclobutrazol on the root activity during annual growth cycle of mango tree to standardize the fertilizer and irrigation management practices of mango trees for sustained fruit production.